Psychosocial Outcomes Among Veteran and Non-Veteran Survivors of Sexual Assault - Holder, Nicholas (Journal of interpersonal violence, 2023)
Although it is well-established that sexual assault results in variable and long-lasting negative impacts on emotional well-being, perceptions of physical health, and relationship functioning, these “psychosocial” outcomes may vary based on the type(s) of sexual trauma experienced. To identify the differential impact of sexual trauma type(s) on psychosocial outcomes among veterans and non-veterans, we conducted a secondary analysis of data from the Comparative Health Assessment Interview Research Study, a large, national survey study sponsored by the Department of Veterans Affairs. Participants included veterans (n = 3588) and non-veterans (n = 935) who endorsed experiencing childhood sexual assault (CSA), adult sexual assault (ASA, outside of military service for veteran participants), and/or military sexual assault (MSA). Eight measures were used to assess psychosocial outcomes: Well-Being Inventory (WBI) health satisfaction and physical health functioning items, Posttraumatic Stress Disorder Checklist, Patient Health Questionnaire (depression symptoms), Generalized Anxiety Disorder Questionnaire, WBI social satisfaction items, WBI social functioning items, and the Multidimensional Scale of Perceived Social Support (social). A profile analysis was used to determine how sexual trauma type(s) influenced the pattern of responding to the eight psychosocial outcome measures. Veteran sexual assault survivors reported poorer psychological outcomes compared to non-veteran sexual assault survivors. Non-veteran sexual assault survivors reported poorer outcomes on the majority of social variables compared to veteran sexual assault survivors. Survivors of MSA-only reported poorer psychosocial outcomes compared to veteran and non-veteran survivors of CSA-only and ASA-only on most of the variables assessed. Survivors of ASA-only reported similar or modestly worse psychosocial outcomes when compared to survivors of CSA-only on the majority of variables assessed. Survivors of different types of sexual trauma reported distinct psychosocial outcomes, suggesting that assessment and treatment needs may differ by trauma type.